Off-label use of targeted therapies in osteosarcomas: data from the French registry OUTC'S (Observatoire de l'Utilisation des Thérapies Ciblées dans les Sarcomes). Issue 1 (December 2015) - Penel-Page, Mathilde; Ray-Coquard, Isabelle; Larcade, Julie; Girodet, Magali; Bouclier, Laure; Rogasik, Muriel; Corradini, Nadège; Entz-Werle, Natacha; Brugieres, Laurence; Domont, Julien; Lervat, Cyril; Piperno-Neumann, Sophie; et al.
Abstract Background The objective of this study is to explore the off-label use of targeted therapies (TTs) for patients with osteosarcoma registered within the French Sarcoma Group – Bone Tumor Study Group (GSF-GETO) national registry. Methods All patients with an osteosarcoma, registered between January 1, 2009 and July 15, 2013 were analyzed. Results Twenty-nine patients with refractory relapsed osteosarcomas received 33 treatment lines of TTs. The median age at the beginning of treatment was 19 years (range 9–72). The median number of previous lines of chemotherapy was 3 (range 1–8). Before inclusion, 3 patients were in second complete remission, 26 were in progression for metastatic relapse. Twenty-three patients received sirolimus (in combination with cyclophosphamide for 18); 5, sunitinib; 4, sorafenib; and one, pazopanib. Stable disease was observed for 45.5 % of patients (95 % Confidence Interval (CI) [20–52.8]). The median Progression-Free Survival (PFS) was 3 months (95 % CI [2–5.4]) for patients treated by sirolimus and 1.8 months (95 % CI [1.3–2.8]) for patients receiving multi-targeted tyrosine kinase inhibitors; 6-month PFS 15 %. The median Overall Survival (OS) was 6.8 months (95 % CI [4.7–12.1]), and one-year OS was 24 %. In a multivariate analysis, PFS was superior for patients receiving sirolimus compared to other TTs (Hazard Ratio (HR) = 2.7, 95 % CI [1.05–7.1]). No toxic death was reported. Grade 3 and 4 toxicities were observed in 27 and 6 % of cases respectively. Conclusion Off-label TTs, especially sirolimus, reported benefit in the treatment of refractory osteosarcomas with an acceptable toxicity profile, including in pediatric population.